Molecular cloning and sequencing of chicken liver fatty acid synthase cDNA. - Holzer, K P (1989)
The complete amino acid sequence of chicken liver fatty acid synthase [acyl-CoA:malonyl-CoA C-acyltransferase (decarboxylating, oxoacyl- and enoyl-reducing, and thioester-hydrolyzing), EC 2.3.1.85] has been determined from the corresponding cDNA sequence. A 5.3-kilobase-pair (kbp) region of cDNA coding for chicken fatty acid synthase has been cloned and sequenced that is contiguous to the 2.3-kbp region previously sequenced [Yuan, Z., Liu, W. & Hammes, G.G. (1988) Proc. Natl. Acad. Sci. USA 85, 6328-6331]. The cDNA codes for the remaining 1677 amino acids of the previously unsequenced region of the protein. The amino acid sequence contains peptides known to be associated with the NADPH binding site of the enoylreductase active center, the acetyl/malonyltransacylase active site, the "waiting" site containing cysteine, and a pyridoxal 5'-phosphate binding site. Locations of the NADPH binding site of the beta-ketoacylreductase active site and of the dehydratase active site are proposed on the basis of protein sequence homologies to catalytic sites in other enzymes. The molecular weight of the complete polypeptide chain is 267,288. A linear functional map of the chicken fatty acid synthase derived from its primary sequence is presented.